2023
DOI: 10.1093/ornithapp/duad014
|View full text |Cite
|
Sign up to set email alerts
|

Global positioning system (GPS) and platform transmitter terminal (PTT) tags reveal fine-scale migratory movements of small birds: A review highlights further opportunities for hypothesis-driven research

Abstract: Studying migration is critically important for understanding the full-annual cycle of migrating birds and aids in management and conservation. In recent years, global positioning system (GPS) and platform transmitting terminal (PTT) tags have become miniaturized, revolutionizing migration research by allowing for higher location accuracy and global coverage for smaller species. We reviewed 116 primary research papers from 2006 to 2021 that reported on GPS- or PTT-tagged small birds (<500 g) during migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 140 publications
2
1
0
Order By: Relevance
“…Our results show a growth in the number of shorebird tracking publications over time, similar to patterns found for other groups of bird (e.g. Geen et al 2019;Iverson et al 2023). Early tracking research focused on medium and large-sized species, with studies on smaller species developing later.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results show a growth in the number of shorebird tracking publications over time, similar to patterns found for other groups of bird (e.g. Geen et al 2019;Iverson et al 2023). Early tracking research focused on medium and large-sized species, with studies on smaller species developing later.…”
Section: Discussionsupporting
confidence: 83%
“…These results are in line with other reviews, which have shown that 93% of transmitter deployments on birds <500 g took place in the northern hemisphere (Iverson et al 2023), where most bird ringing also occurs (Bairlein 2003). This disparity may partly be explained by the fact that in 62% of the publications, the tracked birds were tagged on the breeding grounds, which are typically located in the northern hemisphere (Kraaijeveld 2014), again in line with previous reviews (65%; Iverson et al 2023). Financial inequality can also help explain such geographical biases (Amano & Sutherland 2013).…”
Section: Geographical Scope Of Shorebird Trackingsupporting
confidence: 93%
“…Recent technological advances have led to GPS-tracking devices light enough to be outfitted to some small birds (reviewed in [ 23 ]), providing new opportunities to study breeding-season movements outside territories and to describe a full home range area [ 24 , 25 ]. One major advantage of GPS tracking is that migratory birds tagged during one season can be passively tracked during other times of the year, including in remote areas that are difficult to access, enabling a large array of new ecological research on species and life-stages that are difficult to observe or access.…”
Section: Introductionmentioning
confidence: 99%